Risk-Taking as Moderating Variable for The Impact of Financial Literacy, Financial Inclusion and Digital Technology Utilization on MSMEs’ Performance - Marina Marina; P. Basuki Hadiprajitno (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to find out how the superiority of human resources as MSME actors affects the performance of the MSMEs they manage, with moderate risk taking. The measures used as human resource excellence, or as independent variables are financial literacy, financial inclusion, use of digital technology, and moderated risk taking. Meanwhile, the dependent variable is the performance of MSMEs. The research method uses quantitative experiments, namely to test a proposed hypothesis. Structural Equation Modeling (SEM) data analysis technique using the SMARTPLS4 analysis tool. The research population is the alumni association business forum of SMA Negeri 28 Jakarta which consists of 237 MSME players. Of the 132 respondents who filled out the questionnaire, the data that could be used was 99 research samples. The results of the research show that financial literacy and the use of digital technology have a significant positive effect on the performance of MSMEs, risk taking can moderate the effect of financial literacy on the performance of MSMEs in a significantly positive way, financial inclusion has no significant effect on the performance of MSMEs, risk taking cannot moderate the effect of financial inclusion and use digital technology on the performance of MSMEs. The practical implications that can be made by MSME players by increasing the use of digital technology are effectively helping product marketing, learning facilities, and other conveniences that are often done digitally.